Providing a Model for the Securitization of Bank Claim Collateral through the Capital Market - Ehsan Keivan, Mohammad; Darabi, Roya; Baghani, Ali (Business, Marketing, and Finance Open, 2025)
The objective of this article is to propose a comprehensive conceptual model for the development of securitization of bank claim collateral through the capital market in Iran, designed with an emphasis on financial stability. The study was conducted in 2024 using a mixed qualitative–quantitative methodology. In the qualitative phase, thematic analysis was employed, leading to the identification of six principal dimensions, including legal and regulatory frameworks, information transparency and disclosure systems, risk management and asset quality, institutional and organizational infrastructure, economic and financial market factors, investor participation and behavioral economics, financial technology and innovation, alignment with macroeconomic objectives, and model sustainability and resilience. Qualitative sampling was carried out purposively based on the expertise of banking managers, credit and risk specialists, and capital market practitioners. In the quantitative phase, data were collected through questionnaires developed from qualitative findings and analyzed using Interpretive Structural Modeling (ISM) and MICMAC analysis to determine causal relationships as well as the driving and dependence power of variables. The findings indicated that prioritizing key variables such as risk management, institutional and organizational infrastructure, and directing financial resources toward productive sectors can generate positive cascading effects across other model components. The study provides an operational framework for strategic decision-making, resource allocation, securitization instrument design, and enhancement of investor confidence, thereby contributing to capital market development, increased securities liquidity, improved bank financial soundness, and alignment with national macroeconomic objectives.